Social psychological and developmental perspectives on early sport specialization - Horn, T. S. (Kinesiology Review, 2015)
One of the primary dilemmas surrounding the topic of early sport specialization is whether the practice develops talent or creates long-term psychological problems. The purpose of this paper is to discuss this issue using psychosocial and developmental frameworks. This review begins with an overview of several developmentallybased constructs (e.g., biological maturation, perceived competence, body image, self-identity, motivational orientation) that are relevant to the sport domain. These developmental progressions are then used to address some potential implications for children who begin intensive training and competition at an early age. Next, some socioenvironmental factors are explored, with specific links made to the early sport specialization process. Finally, the paper ends with four recommendations for future research on the topic.